Islamic leviathan - Nasr, Seyyed Vali Reza (Oxford University Press, 2001)
Islamization is commonly seen as the work of Islamist movements who have forced their ideology on ruling regimes and other hapless social actors. There is little doubt that ruling regimes and disparate social and political actors alike are pushed in the direction of Islamic politics by Islamist forces. However, Islamist activism and its revolutionary and utopian rhetoric only partly explain this trend. Here, Nasr argues that the state itself plays a key role in embedding Islam in the politics of Muslim countries. Focusing on Malaysia and Pakistan, Nasr argues that the turn to Islam is a facet of the state's drive to establish hegemony over society and expand its powers and control